Proposing a Framework for Impact Analysis for Low-Code Development Platforms - Overeem, Michiel; Jansen, Slinger (2021 ACM/IEEE International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2021)
Low-code development platforms accelerate software development by facilitating end-user programming. Through higher-level abstractions citizen developers are enabled to develop increasingly complex software systems. While this improves productivity and efficiency it also introduces new challenges in the development process. The evolution of the low-code development platform and the applications built on top of it is one of those challenges. Understanding the impact of changes on the software system is crucial for both the maintenance as well as the improvement of running software. Citizen developers can be supported by direct feedback that reflects how their changes impact the system. Professional developers can use the impact analysis to correctly migrate existing data. Finally, the operations engineers that are responsible for the availability of the platform and the applications can plan seamless upgrades of new versions. Impact analysis should be at the foundations of the development of low-code development platforms. This paper proposes the Impact Analysis for Low-Code Development Platforms framework, a conceptual framework that supports the discussion, research, and implementation of impact analysis. The proposed framework describes the different subsystems and artifacts in a low-code development platform, the different types of professionals involved, and how these professionals can use impact analysis to support their engineering decisions. Through a descriptive case study we discuss the role of impact analysis in an industry low-code development platform. Through the feedback acquired by impact analysis, professionals can stay in control of the evolution of both the applications as well as the low-code development platform itself.